MicroRNA-1-Mediated Inhibition of Cardiac Fibroblast Proliferation Through Targeting Cyclin D2 and CDK6 - Valkov, Nedyalka; King, Michelle E.; Moeller, Jacob; Liu, Hong; Li, Xiaofei; Zhang, Peng (Frontiers in Cardiovascular Medicine, 2019)
MicroRNA-1 (miRNA-1) has been long viewed as a muscle-specific miRNA and plays a critical role in myocardium and cardiomyocytes by controlling myocyte growth and rhythm. We identified that miRNA-1 is expressed in cardiac fibroblasts, which are one of the major non-muscle cells in myocardium and are responsible for cardiac fibrosis in pathological conditions. In this study, we aimed to investigate the effect and mechanism of action of miRNA-1 on cardiac fibroblast proliferation. Subcutaneous angiotensin II (Ang II) infusion via osmotic minipumps for 4 weeks was used to induce myocardial interstitial fibrosis in male Sprague-Dawley rats. MiRNA-1 expression was significantly down-regulated by 68% in freshly isolated ventricular fibroblasts from Ang II-infused rats than that from control rats. Similar results were obtained in adult rat ventricular fibroblasts that were stimulated in culture by Ang II or TGFβ for 48 hrs. Functionally, overexpression of miRNA-1 inhibited fibroblast proliferation, whereas knockdown of endogenous miRNA-1 increased fibroblast proliferation. We then identified and validated cyclin D2 and cyclin-dependent kinase 6 (CDK6) as direct targets of miRNA-1 in cardiac fibroblasts using biochemical assays. Moreover, we showed that the inhibitory effects of miRNA-1 on cardiac fibroblast proliferation can be blunted by overexpression of its target, cyclin D2. In conclusion, our findings demonstrate miRNA-1 expression and regulation in adult ventricular fibroblasts, where it acts as a novel negative regulator of adult cardiac fibroblast proliferation that is at least partially mediated by direct targeting of two cell cycle regulators. Our results expand the understanding of the regulatory roles of miRNA-1 in cardiac cells (i.e., from myocytes to a major non-muscle cells in the heart).